The Potential for Applying Lean Construction in Construction Projects in Manokwari Regency: A Systematic Literature Review - Natalia E Safkaur (Technema: Journal of Intelligent Engineering and Computing, 2026)
The construction industry continues to experience challenges that adversely affect project performance, including schedule delays, resource waste, low productivity, and escalating construction costs. Lean Construction has emerged as a management approach that emphasizes value creation while eliminating non-value-adding activities throughout the construction process. This study aims to evaluate the potential application of Lean Construction in construction projects in Manokwari Regency using a Systematic Literature Review (SLR). The review followed the PRISMA 2020 guideline by systematically identifying, screening, assessing, and synthesizing relevant peer-reviewed publications retrieved from Scopus, ScienceDirect, Google Scholar, Dimensions, and Garuda. The findings indicate that Lean Construction has significant potential to improve labor productivity, reduce material waste, enhance construction quality, shorten project completion time, and increase overall project efficiency. The review further identifies the Last Planner System, Just in Time, Value Stream Mapping, Visual Management, and Continuous Improvement as the most suitable Lean practices for regional construction projects. Nevertheless, successful implementation remains constrained by limited workforce competency, inadequate understanding of Lean principles, logistical challenges, and organizational readiness. The study concludes that Lean Construction offers a promising strategy for improving construction project performance in Manokwari Regency when supported by integrated project management, stakeholder commitment, and continuous capacity development.